Cost models – pillars for efficient cloud computing: position paper. (2013) - Negru, Catalin; Cristea, Valentin
Cost models are fundamental building blocks for cloud computing. Cloud providers offer a very wide portfolio of services, while Cloud clients access them against some financial arrangement. There is a fundamental trade-off between what Cloud provider can offer in terms of resources (software or hardware), services (e.g., storage, e-mail) cost and what Cloud clients are willing to pay. The Cloud cost models today are distinct based on service models: Infrastructure as a Service (IaaS), Platform as a Service (PaaS) and Software as a Service (SaaS). The need to forecast the cost over a period of time imposes building of cost models, which have to be accurate and error free. In this paper, we make a survey and analyse existing cost models in cloud computing and discuss open issues related to the subject.